IMPLEMENTATION TUBERCULOSIS CONTROL PROGRAM WITH DOTS STRATEGY: A CASE STUDY IN BEBESAN COMMUNITY HEALTH CENTER - Rosita Adani Gayo; Jenny Marlindawani Purba; Frida L. Saragih (Jurnal Ilmiah Keperawatan, 2026)
Background: Tuberculosis (TB) remains a significant public health problem in Indonesia. Efforts to control TB is still dealing with various challenges, including suboptimal early detection and high mortality rates due to this disease. Purpose: This study aims to analyze the effectiveness of the TB control program with the DOTS (Directly Observed Treatment Short-course) strategy at the Bebesen Health Center, Central Aceh Regency. Methods: The study used a qualitative method with a case study approach, involving five key informants through in-depth interviews and field observations in Central Aceh Regancy. Results: The results of the study showed that the commitment of the policy maker was not optimal, the TB diagnosis process tended to be passive, drug monitoring (PMO) was inconsistent, and there were obstacles in non-OAT logistics. In addition, the recording and reporting system for treatment results needs to be improved. Analysis of these findings shows the need for increased political commitment, training for PMOs, and improvements in logistics and recording systems. Conclusion: The effectiveness of the TB control program at the Bebesen Health Center needs to be improved through comprehensive improvement steps in order to significantly reduce the number of TB cases in Central Aceh District.